Calibration Scheme for Portable Retroreflectometers of Road Traffic Signs. Issue 4 (October 2020) - He, Huayang; Su, Wenying; Han, Xiaokun; Wang, Rui
Abstract: Portable retroreflectometers are widely used for engineering measurements and are equipped with a set of work plates that are used to fit fitting curves and switch the working curve in the intrinsic software (self-calibration). The measuring principle employed is the substitution method. Therefore, the accuracy of the work plate values and curve-fitting ability of the internal software are important factors related to the accuracy of the instrument's measurement results. A calibration scheme for portable retroreflectometers is proposed in this paper. This scheme not only considers calibration in the laboratory, but also on-site measurements. The work plate values can be obtained by a standard retroreflection measurement system, or by a matching portable retroreflectometer. When the work plate values are obtained through the matching instrument, a set of reference plate values must be obtained first. The reference plates, the color and coefficients of retroreflection of which are similar to those of the work plates, were calibrated by the standard retroreflection measurement system using the direct illuminance method. The reference plates were used to adjust the fitting curve in the internal software of the instrument. The work plates were then measured by the matching instrument to obtain a set of work plate values. The reference plates were measured by a self-calibration portable retroreflectometer, and the relative error between the instrument's results and reference values was calculated.